Evaluation of Non-Newtonian Fluid Flow in Coiled Tubing (International Journal of Geoscience, Engineering and Technology, 2022)
The coiled tubing system is made up of a long and flexible steel tube wound around a coil, which can reach over 6000 meters in length. During operation, part of the tube remains wound on the spool, while the other part is directed into the well. In this tube, different types of fluids, such as water, cement paste and displacement fluid, are pumped in order to ensure the isolation of the well. This work presents three stage of experiment that was carried out with water and xanthan gum solutions that had rheological properties and behavior that approximated a used cement paste. In the first stage of this study, data from pumping water and cement paste in a real well abandonment process were used to validate a mathematical modeling. The simulated data approximated the field data with a mean relative error below 9%. In the second stage experiments were carried out with xanthan gum solution at a concentration of 0.5 lb bbl-1, and temperatures of 30ºC and 40ºC. The objective of this study was to verify if the model proposed by the author is valid for different concentrations and temperatures. Finally, in the third stage of the study, simulations were carried out in order to obtain the maximum pumping capacity of the system, with the installation of a new pump. The simulated data shown that the water flow reached the turbulent regime with a maximum pumping flow of 2 m3 h-1, while the flow of the xanthan gum solution did not reach the turbulent regime, even reaching a maximum flow of 3 m3 h-1.